2021
DOI: 10.1002/smll.202103086
|View full text |Cite
|
Sign up to set email alerts
|

Automated Optical Tweezers Manipulation to Transfer Mitochondria from Fetal to Adult MSCs to Improve Antiaging Gene Expressions

Abstract: Mitochondrial dysfunction is considered to be an important factor that leads to aging and premature aging diseases. Transferring mitochondria to cells is an emerging and promising technique for the therapy of mitochondrial deoxyribonucleic acid (mtDNA)‐related diseases. This paper presents a unique method of controlling the quality and quantity of mitochondria transferred to single cells using an automated optical tweezer‐based micromanipulation system. The proposed method can automatically, accurately, and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 69 publications
(86 reference statements)
1
20
0
Order By: Relevance
“…The number of mitochondria transferred into recipient cells can be controlled by adjusting the concentration of the isolated mitochondria suspension used. Compared with the traditional coculture method ( 16 , 24 ) and the recently proposed OT-based method ( 14 ), the method proposed in the present study can achieve quantitative control of mitochondrial transfer into recipient cells at the single-cell level while maintaining a high mitochondria transfer efficiency of 75% and a high throughput, generating 2 × 10 6 mitochondria-transferred cells in 2.5 hours (0.5 hours for generating droplets containing the cells and isolated mitochondria and 2 hours for the mitochondrial transfer process in droplets). The previous work showed that the number of mitochondria transferred into recipient cells increased with the time used for the transfer process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of mitochondria transferred into recipient cells can be controlled by adjusting the concentration of the isolated mitochondria suspension used. Compared with the traditional coculture method ( 16 , 24 ) and the recently proposed OT-based method ( 14 ), the method proposed in the present study can achieve quantitative control of mitochondrial transfer into recipient cells at the single-cell level while maintaining a high mitochondria transfer efficiency of 75% and a high throughput, generating 2 × 10 6 mitochondria-transferred cells in 2.5 hours (0.5 hours for generating droplets containing the cells and isolated mitochondria and 2 hours for the mitochondrial transfer process in droplets). The previous work showed that the number of mitochondria transferred into recipient cells increased with the time used for the transfer process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a rather simple process, the success of the coculture method is dependent on many uncontrollable factors, which might determine the unsatisfactory cell metabolism recovery rate of recipient cells in a previous work (~0.2%) ( 16 ). An automated optical tweezers (OT)–based manipulation system was used for qualitative and quantitative mitochondrial transfer ( 14 ) to reduce the influence from uncontrollable factors. The OT-based system could precisely pick up the healthy mitochondria and transport them to the target recipient cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTs have been effectively used to investigate numerous biological applications in recent years 21 , 59 , 60 . As demonstrated in Fig.…”
Section: Micro/nanomanipulation Methods For Single-cell Surgerymentioning
confidence: 99%
“…Subsequently, the OT is now being used in the investigation of an increasing number of biochemical and biophysical processes [23][24][25][26][27][28][29][30][31][32][33]. After decades of developments, convenient commercial OT machines and automatic manipulation systems with microfluidic chips [34][35][36][37] are becoming available and popular. Many easy-to-use OT products have been promoted.…”
Section: Introductionmentioning
confidence: 99%